2023
DOI: 10.1007/s10796-023-10417-2
|View full text |Cite
|
Sign up to set email alerts
|

A Framework of Environmental, Personal, and Behavioral Factors of Adult Learning in Online Communities of Practice

Abstract: Adult learning is a complex phenomenon that takes place over an adult’s lifetime and is not limited to a particular age. It includes a set of activities to enhance life through improving skills, knowledge and capabilities. The foundational theories of adult learning, such as andragogy theory, place the individual adult centre stage and differentiate adult learning from formal learning. They also shift the focus from the individuals to the environment in which adult learning takes place. In line with this movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 88 publications
1
4
0
Order By: Relevance
“…Moreover, the hypothesized positive effect of personal factors-self-efficacy and individual benefits-on continuance intention in VCoPs is supported. This finding is in line with most of the empirical studies developed in this area (e.g., [31,33,57]). Feeling able to use the technology successfully to achieve goals and obtain individual rewards leads to overall personal improvement from participating in the VCoP, thus encouraging members' continued participation in the community and potentially increasing their wellbeing due to personal fulfilment, both from perceived competence and objective gains.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, the hypothesized positive effect of personal factors-self-efficacy and individual benefits-on continuance intention in VCoPs is supported. This finding is in line with most of the empirical studies developed in this area (e.g., [31,33,57]). Feeling able to use the technology successfully to achieve goals and obtain individual rewards leads to overall personal improvement from participating in the VCoP, thus encouraging members' continued participation in the community and potentially increasing their wellbeing due to personal fulfilment, both from perceived competence and objective gains.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, prior research reported that identification has a positive effect on the quality and quantity of the knowledge contributed and permanence in VCs [29,71]. Thus, previous studies within the literature have shown the importance of fulfilling this social need as a means of nurturing members' participation [57]. We argue that reciprocity and identification are motivational factors that will affect the intention to continue in VCoPs.…”
Section: Motivational Factorsmentioning
confidence: 58%
See 2 more Smart Citations
“…According to social cognitive theory (Bandura, 1977(Bandura, , 2023, learning occurs in a social context with a dynamic and reciprocal interaction of the person, environment, and behavior. Linking to implicit theories, the theory suggests that people's inner beliefs about abilities are learned from the interaction of person, environment, and behaviors (Abedini et al, 2023). It further highlights that people's inner beliefs function as general principles for directing and influencing intentional behaviors, and people accept their inner beliefs as true regardless of evidentiary support, which impacts their motivational tendencies and, subsequently, outcome behaviors (Rad et al, 2023;Hamann et al, 2024).…”
Section: The Perspective Of Social Cognitive Theorymentioning
confidence: 97%